Andrographis paniculata and Its Bioactive Diterpenoids Against Inflammation and Oxidative Stress in Keratinocytes - Eugenie Mussard; Sundy Jousselin; Annabelle Cesaro; Brigitte Legrain; Eric Lespessailles; Eric Esteve; Sabine Berteina-Raboin; Hechmi Toumi (MDPI AG, 2020)
Andrographis paniculata was widely used in traditional herbal medicine to treat various diseases. This study explored the potential anti-aging activity of Andrographis paniculata in cutaneous cells. Human, adult, low calcium, high temperature (HaCaT) cells were treated with methanolic extract (ME), andrographolide (ANDRO), neoandrographolide (NEO), 14-deoxyandrographolide (14DAP) and 14-deoxy-11,12-didehydroandrographolide (14DAP11-12). Oxidative stress and inflammation were induced by hydrogen peroxide and lipopolysaccharide/TNF-α, respectively. Reactive oxygen species (ROS) production was measured by fluorescence using a 2',7'-dichlorofluorescein diacetate (DCFH-DA) probe and cytokines were quantified by ELISA for interleukin-8 (IL-8) or reverse transcription-quantitative polymerase chain reaction (RT-qPCR) for tumor necrosis factor-α (TNF-α). Hyaluronic acid (HA) secretion was determined by an ELISA. Our results show a decrease in ROS production and TNF-α expression by ME (5 µg/mL) in HaCaT under pro-oxidant and pro-inflammatory conditions, respectively. ME protected HaCaT against oxidative stress and inflammation. Our findings confirm that ME can be used for the development of bioactive compounds against epidermal damage.